The utilization of Papaya seed powder (Carica Papaya L.) against the Selar fish Protein levels (Selaroides leptolepis) - Sahara Sahara; Djufri Djufri; Safrida Safrida; Supriatno Supriatno; Khairil Khairil (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2020)
This research aims to determine the influence of papaya seed powder on the level of protein found in selar fish. This research is useful to gived information on the utilization papaya seeds as a natural ingredient to fresh fish to the community. This research was conducted for 4 months from Juli-October 2018, protein test conducted in the Food Analysis Laboratory of THP (Food Technology) study Program Faculty of Unsyiah Agriculture, Banda Aceh. The analysis used for protein testing is analysis of variants (ANOVA) whereas the data analysis technique used for data is completly randomited design (CRD) with six treatments and three times repeated. The concentration treatment of papaya seed powder also has a noticeable effect on fresh fish protein levels. Selar fish are given treatment with papaya seed powder with a concentration of 100% has a percentage of protein content as much as 15.32%Keywords: Selar Fish, papaya seed powder, protein level.Penelitian ini bertujuan untuk mengetahui pengaruh serbuk biji pepaya terhadap kadar protein yang terdapat pada ikan selar. Manfaat dari penelitian ini yaitu dapat memberikan informasi mengenai pemanfaatan biji pepaya sebagai bahan alami terhadap ikan selar segar kepada masyarakat. Penelitian ini dilaksanakan selama 4 bulan sejak bulan Juli-Oktober 2018, uji protein dilakukan di Laboratorium Analisis Pangan Program Studi THP (Teknologi Hasil Pangan) Fakultas Pertanian Unsyiah, Banda Aceh. Analisis yang digunakan untuk uji protein adalah analisis varian (ANAVA) sedangkan teknik analisis data yang digunakan untuk data adalah Rancangan Acak Lengkap (RAL) dengan enam perlakuan dan tiga kali ulangan. Perlakuan konsentrasi serbuk biji pepaya juga berpengaruh nyata pada kadar protein ikan selar segar. Ikan selar yang diberi perlakuan dengan serbuk biji pepaya dengan konsentrasi 100% memiliki persentase kadar protein sebanyak 15,32%.Kata kunci: Ikan selar, serbuk biji pepaya, kadar protein